Peranah Cita Hukum dalam Pembentukan Hukum Nasional - Riri Nazriyah (Jurnal Hukum IUS QUIA IUSTUM, 2002)
The formation of national law recently stressed more on formal and positivistic legal aspect so that the product of law created is more practical and pragmatic. Forthis reason, it need storenovate in the process o flaw formation it self by referring to the value and idea of Indonesian law. Besides that, the law formation is still stronger philosophically and sociologically.